2018
DOI: 10.1186/s40703-018-0077-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on bearing capacity of single stone column

Abstract: Stone columns are an efficient ground improvement technique for treating problematic soils. The confidence in the prediction accuracy of bearing capacity remains unsatisfactory. This paper aims to investigate the bearing capacity of single stone column using three-dimensional numerical analysis. Failure modes were observed and the effect of key parameters such as column's friction angle, undrained shear strength of surrounding soil and modular ratio were investigated. Numerical results showed bulging and a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…E. T, 1995). Furthermore, additional research has identified three distinct failure modes for single columns: shearing failure, bulging failure, and general punching failure, with notable contributions from Debbabi et al (2020), Ng (2018), and Yousfi et al (2023.…”
Section: Introductionmentioning
confidence: 99%
“…E. T, 1995). Furthermore, additional research has identified three distinct failure modes for single columns: shearing failure, bulging failure, and general punching failure, with notable contributions from Debbabi et al (2020), Ng (2018), and Yousfi et al (2023.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever reinforced soft soil supports a transport infrastructure such as the railways or highways, the ground surface is subjected to cyclic loads apart from the usual static loads imposed by the regular traffic [14][15][16]]. Significant experimental and numerical studies on stone column reinforced soft soil behavior were done in the recent past [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Ng [22] conducted three-dimensional numerical modeling of stone columns to determine the bearing capacity of a single stone in soft soil and concluded that bearing capacity of the stone column was influenced by friction angle of the column and surrounding soil. The combination of bulging and punching failure was reported in a single column.…”
Section: Introductionmentioning
confidence: 99%